A Morphological Analysis of Tense in Mambwe Language - Pethias Siame (PT Mattawang Mediatama Solution, 2023)
Guthrie (1948) classifies Mambwe as M15. The language is spoken in Mbala and Senga districts in Northern Province of Zambia. Nurse and Philipson (1999) have characterized Mambwe as originating from Fipa language in Southern Tanzania. The paper outlines the rules governing tense categorization and evaluates the verbal structure of tense in Mambwe language. The study employed the qualitative approach and elicitation methodology to collect data. Using descriptive and Lexical Morphology (LM) theoretical underpinnings, the article identifies the forms or categories of tense and their respective structures in Mambwe language. The study shows that tense in Mambwe language is as attested by other Bantu languages in terms of the present, past and the future tenses with their corresponding progressive counterparts.